Critical thinking: a reveal in virtual learning environments - Taborda, Yarmin (2020)
Think about critical thinking as one of the aims of education in Colombia is a major objective, but stablish it as a reveal in virtual learning environments is not just a challenge, it is a commitment to revigorate and establish strategies that make this objective feasible. The research “Show up/Appear  of critical thinking in virtual learning environments” developed in an institution that develops its learning processes under the e-learning and b-learning modalities, was carried out under the qualitative - inductive approach that investigated the elements that allow the emergence of critical thinking in virtual environments and at the same time, determined the challenges that a teacher must assume to make this possible.